2022
DOI: 10.1021/acsomega.2c00725
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Genesis of the Permain Hydrocarbon in the Northeast of the Dongdaohaizi Depression, Junggar Basin, China

Abstract: Dongdaohaizi area is an important hydrocarbon-rich depression in the Junggar Basin. Early resource evaluation has revealed that it has superior hydrocarbon generation conditions. No major exploration breakthrough has been observed in the hydrocarbon from the Permian Pingdiquan Formation source rocks, which are widely distributed and have a large sedimentary thickness. The unclear recognition of the genesis, the sources, and the hydrocarbon evolution history of the formation seriously restricted further explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Known to all, many of the terpanes in petroleum originate from lipidoids in bacterial (prokaryotes) membranes. ,,, Moreover, tricyclic terpenoids (C 19 –C 29 ) are derived from regular C 30 isoprenes, and the high abundance of tricyclic terpenoids may also be related to the original algae. , However, hopane mainly exists in prokaryotes and higher plants, while prokaryotes are lacking . Besides, some specific TTs represent markers of terrestrial organic matter input into coal or source rocks (C 19 –C 20 TT) and typical marine or lacustrine organic matter input into source rocks (C 23 –C 24 TT), respectively. ,,,, In this study, we used a biomarker recovery method to correct them, and the results were particularly significant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Known to all, many of the terpanes in petroleum originate from lipidoids in bacterial (prokaryotes) membranes. ,,, Moreover, tricyclic terpenoids (C 19 –C 29 ) are derived from regular C 30 isoprenes, and the high abundance of tricyclic terpenoids may also be related to the original algae. , However, hopane mainly exists in prokaryotes and higher plants, while prokaryotes are lacking . Besides, some specific TTs represent markers of terrestrial organic matter input into coal or source rocks (C 19 –C 20 TT) and typical marine or lacustrine organic matter input into source rocks (C 23 –C 24 TT), respectively. ,,,, In this study, we used a biomarker recovery method to correct them, and the results were particularly significant.…”
Section: Resultsmentioning
confidence: 99%
“…9,34 As shown in Figure It is well known that the similar maturity of crude oil and source rock is a prerequisite for oil−source correlation. 4,10,20,35 C 27 TAS 20S/(20S + 20R) was derived based on the calculation of the relative content of long-chain TASs proposed by Zhang et al 36 As shown in Figure 8b, three families of crude oils have relatively high C 27 TAS 20S/(20S + 20R) and C 28 TAS 20S/(20S + 20R) ratios, indicating that crude oils should be the product from the maturity stage of the source rock. The maturity of most crude oil samples of family A1 is the closest to that of Permian source rocks, indicating that they may have a potential affinity.…”
Section: Stages 3 and 4 Peters And Moldowanmentioning
confidence: 99%
See 1 more Smart Citation